The Development and Evaluation of E-Management Platform for Patient-reported Outcomes Research Based on Business Process Improvement Theory - Li, Danyu (My University, 2021)
Background Patient-reported outcomes (PROs) refer to the health-related information coming directly from patients without any explanation by the doctors or others. It is of great significance for patients to participate in medical decision-making, have a higher quality of care，and have a better medical outcome. Therefore, patient-reported outcomes measurements (PROMs) have important clinical value. Patient-reported Outcomes Measurement Information System (PROMIS) is one of the most accurate PROMs led by NIH and focuses on health-related big data's scientific characteristics. PROMIS advocates cross-population, cross-region, and cross-disease studies and is widely recognized among the research community. PROMIS Health Organization (PHO) now promotes the global implementation of PROMIS by setting up PROMIS National Center (PNC) in various countries, and PNCs organize the research cooperation with many research groups to promote PROMIS. PROMIS China Center is one of the PNCs that takes charge of the PROs cooperative research with many research teams to promote PROMIS in China. Due to the diverse tasks, complex procedures, and low efficiency of the current cooperative management mode of PROMIS China Center, it cannot meet the efficient research management requirements. Therefore, it is necessary to analyze the needs, improve the process, and build an E-management platform under the guidance of business improvement theory to improve the management efficiency of the patient-reported outcome research and eventually promote PROMIS in China. Objectives The general purpose of this research is to improve the management process of patient-reported outcomes research based on the business process improvement theory and develop an E-Management platform as well as evaluate the usability of the E-management platform. Purpose one: The need analysis of the E-management platform for the patient-reported outcomes research; Purpose two: The framework construction of the E-management platform for patient-reported outcomes research; Purpose three: The development of the E-management platform for patient-reported outcomes research; Purpose four: The usability evaluation of the E-Management Platform for Patient-reported outcomes research. Methods The study was comprised of 4 parts： Part1: The need analysis of the E-management platform for the patient-reported outcomes research Based on business improvement theory (ESIA theory), the researcher conducted the semi-structured qualitative interviews, including five rounds of focus group interviews with 5 management staffs of the PROMIS China Center and one-on-one interviews with 11 cooperative team members to know the current management process of patient-reported outcomes research, the problems of current management process, and the need for the E-management platform. Part2: The framework construction of the E-management platform for patient-reported outcomes research The researcher held a brainstorming discussion with 13 management staffs to improve the current management process based on business improvement theory; Meanwhile, the researcher accomplished the literature study about the patient-reported outcomes research E-management platforms of other countries and analyzed the framework; Then, the researcher combined the results of need analysis, brainstorming, and literature study to draw the preliminary framework of the patient-reported outcomes research E-management platform; Finally, the researcher held an expert group meeting with 7 experts from the field of both nursing research and software engineering to revise the preliminary framework and make a final framework. Part3: The development of the E-management platform for patient-reported outcomes research The researchers organized and coordinated close cooperation among experts in different fields. Based on the final framework of the E-management platform formed in the early stage, the researchers adopted the human-centered concept and the agile development method to develop the E-management platform with 3 software engineers. Part4: The usability evaluation of the E-Management Platform for Patient-reported outcomes research The researcher implemented the formative usability evaluation during the process of development to find the problems about the interface, like font and module; Then the researcher implemented the summarized usability evaluation by task analysis and semi-structured interviews with 15 users，including 5 management staffs of the PROMIS China Center and 10 cooperative team members. The evaluation outcomes were reported after data analysis. Results Part1: The need analysis of the E-management platform for the patient-reported outcomes research The qualitative research results show the: ① PROMIS translation, validation, clinical application management processes, and the researcher presented them in text and flow chart. ② The current process's problems, like the current management process is tedious; the current management process involves too much paper materials; it is difficult for management staffs to supervise the process. ③ the need for the E-management: all the participants said they need the E-management platform and expressed their specific needs. Part2: The framework construction of the E-management platform for patient-reported outcomes research The brainstorming efficiently improved the management process, and the improved process was shown with text and flowchart; The literature study presented the framework of the Netherlands PROMIS E-management platform; the researcher drew a preliminary framework of the E-management platform under the guidance of need analysis, improved management process, and Netherlands PROMIS E-management platform, which contains 7 first-level modules, and 5 second-level modules. After the expert group meeting, the final framework was constructed, which includes 6 first-level modules: "Home", " Introduction ", "PROMIS Measurement", "News Center", "Resources", and " Research Cooperation", 16 second-level modules, and the content covered by the second-level modules. Part3: The development of the E-management platform for patient-reported outcomes research The researchers demonstrated the preliminary framework of the E-management platform to the software engineers, and we worked jointly to complete the development of the E-management platform after the steps of requirement clarification, design, development, testing, and release. Part4: The usability evaluation of the E-Management Platform for Patient-reported outcomes research During the formative usability evaluation, the researcher found many problems, and they were all solved by software engineers; During the summarized usability evaluation, we demonstrated the platform in terms of effectiveness, efficiency, and satisfaction. Based on the scores of the usability evaluation questionnaire after the test: system usefulness is 5.2 (from management staffs) and 5.8 (from cooperative team members), information quality is 6.8 (from management staffs) and 6.0 (from cooperative team members), interface quality is 5.4 (from management staffs) and 5.9 (from cooperative team members), and overall evaluation is 6.0 (from management staffs) and 6.2 (from cooperative team members). Through qualitative interviews, we understand the user experience of the platform. The interview data shows two topics related to usability. By combining quantitative and qualitative outcomes, the researcher thinks that the E-management platform's usability is generally good, but there are still some shortcomings. Conclusions Both the management staffs and cooperative team members of the PROMIS China Center have a high level of need for the E-management platform. The final framework based on need analysis and process improvement is good guidance for developing the E-management platform. The usability evaluation shows that the E-management platform has a good usability and can help manage the patient-reported outcomes cooperative research. It will be able to enhance the management efficiency of patients-reported outcomes research extensively and accelerate the rapid promotion of PROMIS in China.
Keywords: Patient-reported Outcomes, Patient-reported Outcomes Measurement Information System, E-management platform, ESIA Theory, Business Process Improvement